THE EFFECT OF PRIZE DRAW, PERCEPTION OF SERVICE QUALITY, AND MOBILE BANKING SERVICES ON SAVING INTEREST (Study at Bank Rakyat Indonesia, Bekasi Harapan Indah Branch) - Yudhistira Riza R; I Made Sukresna (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Bank Rakyat Indonesia (BRI) as a state-owned bank has an important role in increasing financial inclusion in society. One of the strategies implemented is to attract customers to save through a prize draw program, improving service quality, and developing digital services such as mobile banking. This study aims to analyze the effect of Prize Draws, Perception of Service Quality, and Mobile Banking Services on Saving Interest of BRI Bank Bekasi Harapan Indah Branch customers. This research method uses a quantitative approach with a survey method. The sample was determined through a simple random sampling technique, with a population of 700 people and the determination of the number of samples using the Krejcie and Morgan formula, so that 250 respondents were obtained. Data were analyzed using multiple linear regression with the help of SPSS version 26. The results of the study indicate that the three independent variables, namely Prize Draw (t = 4.315; sig = 0.000), Perception of Service Quality (t = 4.053; sig = 0.000), and Mobile Banking Services (t = 4.934; sig = 0.000), have a positive and significant effect on customer Savings Interest. The coefficient of determination (R Square) value of 0.453 indicates that 45.3% of the variation in customer savings interest can be explained by the three variables, while the remaining 54.7% is explained by other factors outside this research model. The implications of this study emphasize the importance for management at the branch level to continue to encourage the use of BRImo as an innovative and safe mobile banking service, consistently improve service quality, and develop attractive prize draw programs in order to strengthen customers' interest in saving sustainably.